Industrierenten und Lohnsetzungsverhalten: gibt es Indizien für die Insider-Outsider Hypothese? - Joachim Möller (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– The insider-outsider theory is one of the approaches with which the persistence of unemployment can be accounted for. The central hypothesis says that the insiders, in other words the 'job holders', drive the wage level above the market-clearing level, thus creating a barrier that prevents new hirings. Due to the existence of hiring costs, e.g. search costs, training costs and the costs for lay-offs e.g. redundancy payments, insiders possess market power. According to the insider-outsider theory, insiders exploit this market power in order to expropriate rents. This paper first examines whether there is evidence of the existence of such rents. Following more recent articles in the literature, we measure the size and temporal course of the rents on the basis of inter-industry wage differentials. These are estimated and analysed using data from the IAB employment sample. Furthermore we look into the hypothesis derived from the insider-outsider theory which says that industries with comparatively high rents demonstrate a high average employment duration. Finally we test a specific wage formation pattern that is expected in the case of insider behaviour (comparatively high wage increases during periods of economic recovery). The results show that there is indeed some evidence that 'job holders' cream off rents to a certain extent. In the industries with high rents there are indications of overly high wage increases particularly during periods of expansion. However, the results of some of the estimates are only weakly statistically firm. Further research is therefore needed in order to substantiate (or refute) the empirical evidence of the insider-outsider hypothesis.
Keywords: 330; Lohnhöhe; Lohnunterschied - Messung; Lohnentwicklung; Lohnfindung; Lohnstruktur - Indikatoren; Indikatorenbildung; Wirtschaftszweige; Betriebszugehörigkeit; zwischenbetriebliche Mobilität; Insider-Outsider-Theorie; Stammbelegschaft; Wirtschaftspolitik; Lohnpolitik; IAB-Regionalstichprobe; USA; Bundesrepublik Deutschland